Relaxin protects cardiac muscle cells from hypoxia/reoxygenation injury: involvement of the Notch‐1 pathway. Issue 1 (23rd October 2014) - Boccalini, Giulia; Sassoli, Chiara; Formigli, Lucia; Bani, Daniele; Nistri, Silvia
Abstract : In animal models, the cardiotropic hormone relaxin has been shown to protect the heart against ischemia and reperfusion‐induced damage, acting by multiple mechanisms that primarily involve the coronary vessels. This in vit ro study evaluates whether relaxin also has a direct protective action on cardiac muscle cells. H9c2 rat cardiomyoblasts and primary mouse cardiomyocytes were subjected to hypoxia and reoxygenation. In some experiments, relaxin was added preventatively before hypoxia; in others, at reoxygenation. To elucidate its mechanisms of action, we focused on Notch‐1, which is involved in heart pre‐ and postconditioning to ischemia. Inactivated RLX was used as negative control. Relaxin (17 nmol/L, EC50 4.7 nmol/L), added 24 h before hypoxia or at reoxygenation, protected against cardiomyocyte injury. In fact, relaxin significantly increased cell viability (assayed by trypan blue and 3‐(4, 5‐dimethylthiazol‐2‐yl)‐2, 5‐diphenyl tetrazolium bromide), decreased apoptosis (assayed by TUNEL and bax/bcl‐2 ratio), and reduced nitroxidative damage (assayed by nitrotyrosine expression and 8‐hydroxy‐deoxyguanosine levels). These effects were partly attributable to the ability of relaxin to upregulate Notch‐1 signaling; indeed, blockade of Notch‐1 activation with the specific inhibitor DAPT reduced relaxin‐induced cardioprotection during hypoxia and reoxygenation. This study adds new mechanistic insights on the cardioprotective role of relaxin on ischemic and oxidative damage—Boccalini, G., Sassoli, C., Formigli, L., Bani, D., Nistri, S., Relaxin protects cardiac muscle cells from hypoxia/reoxygenation injury: involvement of the Notch‐1 pathway. FASEB J. 29, 239–249 (2015). www.fasebj.org